Fractional CO2 laser micropatterning of cell-seeded electrospun collagen scaffolds enables rete ridge formation in 3D engineered skin. (15th January 2020) - Blackstone, Britani N.; Malara, Megan M.; Baumann, Molly E.; McFarland, Kevin L.; Supp, Dorothy M.; Powell, Heather M.
Abstract: Rete ridges are interdigitations of the epidermis and dermis of the skin that play multiple roles in homeostasis, including enhancing adhesion via increased contact area and acting as niches for epidermal stem cells. These structures, however, are generally absent from engineered skin (ES). To develop ES with rete ridges, human fibroblast-seeded dermal templates were treated with a fractional CO2 laser, creating consistently spaced wells at the surface. Constructs with and without laser treatment were seeded with keratinocytes, cultured for 10 days, and grafted onto athymic mice for four weeks. Rete-ridge like structures were observed in the laser-patterned (ridged) samples at the time of grafting and were maintained in vivo . Ridged grafts displayed improved barrier function over non-lasered (flat) grafts at the time of grafting and 4 weeks post-grafting. Presence of ridges in vivo corresponded with increased keratinocyte proliferation, epidermal area, and basement membrane length. These results suggest that this method can be utilized to develop engineered skin grafts with rete ridges, that the ridge pattern is stable for at least 4 weeks post-grafting, and that the presence of these ridges enhances epidermal proliferation and establishment of barrier function. Statement of significance: Rete ridges play a role in epidermal homeostasis, enhance epidermal-dermal adhesion and act as niches for epidermal stem cells. Despite their role in skin function, these structures are not directly engineered into synthetic skin. A new method to rapidly and reproducibly generate rete ridges in engineered skin was developed using fractional CO2 laser ablation. The resulting engineered rete ridges aided in the establishment of epidermal barrier function, basement membrane protein deposition and epidermal regeneration. This new model of engineered skin with rete ridges could be utilized as an in vitro system to study epidermal stem cells, a testbed for pharmaceutical evaluation or translated for clinical use in full-thickness wound repair. Graphical abstract: Image, graphical abstract